A utilização do látex presente no Mamoeiro (Carica papaya. L) como amaciante natural para alimentos na comunidade rural Alvorecer da Esperança-Rosquelícia, Abaetetuba-Pará - COSTA, Eloane VIlhena Pantoja da (2019)
This article discusses the knowledge that traditional communities possess, emphasizing the traditional knowledge that the individuals of the Dawn of Hope community enjoy, regarding the use of papaya latex as a food softener. The objective of this work is to carry out a survey about traditional knowledge regarding the use of latex as food softener. This research was developed through bibliographical review and field research, with observations and applications of semi-structured questionnaires for community residentes. The data were quantitatively-descripive and qualitative. It can be seen that 82% of the interviewees use papaya latex as a softener to feed mainly on the meat, stomach and cattle paw. In addtion the individuals who use this knowledge have diferente age groups, With the result that they are preserving the local culture and passing on from generation to generation.